Analisis Pendapatan Dan Kelayakan Usaha Pada Pabrik Tahu Sumber Rejeki Kelurahan Wae Kelambu, Kecamatan Komodo Kabupaten Manggarai Barat - Agusto Hutrik, Liberatus; Quartina Pudjiastuti, Agnes; Puri Nurani, Maria (BiSTeK Pertanian, 2024)
Along with increasing population growth, there are also more and more businesses in the field of food processing because food is the main human need. One of the food products that are well known among the public is tofu. Tofu is one of the staple foods in Indonesia. A business feasibility study is a study about whether or not a business is carried out profitably on an ongoing basis. Tofu agroindustry Sumber Rejeki is a soybean processing industry into tofu. The Sumber Rejeki tofu agroindustry is located in Nggorang, Komodo District, West Manggarai Regency. A business that is run certainly requires a proper planning and calculation. The purpose of this study was to determine the cost, income and business feasibility of the tofu source of fortune agroindustry in Nggorang, Komodo District, West Manggarai Regency. The analysis used in this research is the analysis of Costs and Revenues, R/C Ratio, Net Present Value (NPV), and Internal Rate Of Return (IRR). The results showed that the Sumber Rejeki tofu business in Nggorang Komodo District, West Manggarai Regency obtained a profit with a value of TC > TR or Rp. 216,000,000 > Rp. 111,636,607, while the results of the feasibility analysis of Sumber Rejeki's tofu business in Ngorang, Komodo Subdistrict, West Manggarai Regency were feasible to use. R/C Ratio > 1 or R/C Ratio = 1.75 > 1, NPV > 0 or NPV = 753.727.492 > 0, IRR > i or IRR = 80.9 % > 4.27%. That means that the Sumber Rejeki tofu business in Nggorang, Komodo District, West Manggarai Regency is profitabel and worth working on.